KANGAROO MOTHER CARE DAN PIJAT BAYI EFEKTIF MENINGKATKAN BERAT DAN PANJANG BADAN PADA BAYI BERAT LAHIR RENDAH - Siti Maryati (MEDIA ILMU KESEHATAN, 2014)
Background : Based on the results of the annual report in the care services of Public General Hospital Wates Yogyakarta in NICU department. Periodic monitoring results in 2012 that 63.16% (of all infant deaths) due to LBW . Efforts are already underway to increase in LBW infants BB in Public General Hospital Wates Yogyakarta is the Kangaroo Mother Care (KMC). Each case LBW done KMC treatment at least 2-3 hours per day by his family. Method of Infant Massage has been done in some hospitals but not yet implemented at this hospital . Objective : The objective of this study was to determine the effectiveness of Kangaroo Mother Care (KMC) and Infant Massage to Increased Body Weight and Length in Low Birth Weight Infants in the NICU hospitals Wates Kulon Progo . Methods : This study used a quasi-experimental research design. The experimental group was Newborns with low birth weight who were given the intervention of Kangaroo Mother Care (KMC) and Infant Massage while the control group was Newborns with low birth weight who were given the intervention of Kangaroo Mother Care (KMC) only. After the intervention for at least 3 days, both groups are seen gaining weight and body length, then see the difference. The sample in this study were all newborns with low birth weight were treated diruang Wates Kulon Progo Hospital NICU during the study met the inclusion criteria and had a total of 18 respondents to the experimental group and 18 respondents for the control group). Independent variable is the Kangaroo Mother Care (KMC) and Infant Massage, the dependent variable is the Weight and Body Length Results : The results of measurements preintervensi Body Weight between experimental and control groups were homogeneous with a mean weight (p value 0.629) and Body Length (p value 0.169) . Difference in the mean increase in Body Weight-fed babies and intervention KMC Infant Massage with KMC at 6.277 grams per day. The mean increase in Body Weight -fed babies and Infant Massage KMC intervention is greater than the average Body Weight infants given KMC intervention, but was not statistically significant (p 0.794). Difference in the mean increase in infants fed NT intervention KMC and Infant Massage with KMC at 0.583 cm per day. The mean increase in NT intervention KMC infants fed higher than the average of NT infants given KMC intervention and Infant Massage, but were not statistically significant (p 0.208) Conclusion : Intervention KMC and Infant Massage can effectively to improve the Body Weight and Body Length but it was not statistically significant . Keywords : LBW, KMC and Infant Massage.